Studi Literatur: Analisis Berpikir Komputasi Siswa dalam Pembelajaran Matematika - Wulan Dari; Yahfizham Yahfizham (LPPM Politeknik Pratama, 2024)
Computational thinking is a way of thinking that students must have. Currently, many students do not yet know how computing can be applied in mathematics learning. For this reason, this research focuses on analyzing students' computational thinking in mathematics learning. This research takes the type of literature study research by identifying and evaluating the results of previous research. Data analysis was carried out using an interactive model which uses 4 steps in the analysis stages, namely: 1) Data collection, 2) Data condensation, 3) Data presentation and 4) Data verification. This research identified 3 previous articles. From the results of this research, it was found that computational thinking in mathematics learning means that students can relate mathematical concepts to the real world, motivate learning and can link mathematics with everyday life.